Why Did Teachers Organize? Feminism and Socialism in the Making of New York City Teacher Unionism. Issue 2 (July 2021) - Phelps, Christopher
Abstract : What prompted New York City teachers to form a union in the Progressive Era? The founding of the journal American Teacher in 1912 led to creation of the Teachers' League in 1913 and then the Teachers Union in 1916, facilitating formation of the American Federation of Teachers (AFT). Despite historiographical claims that teacher union drives needed a focus on bread-and-butter issues to succeed, ideals of educational democracy and opposition to managerial autocracy motivated the Teachers' League. Contrary to claims that early New York City teacher unionism was unrepresentative because dominated by radical male Jewish high-school instructors, heterogeneous majorities of women and elementary school teachers formed the Teachers' League and Teachers Union leaderships. Board of Education representation, maternity leave, free speech, and pensions were aims of this radically democratic movement led by socialists and feminists, which received demonstrably greater mass teacher support than the conservative feminism of a rival association.